Implikasi Transformasi Digital terhadap Hak Upah Pekerja Berdasarkan Peraturan Perundang-Undangan - Agustian, Muhamad Yosi (Lex Librum : Jurnal Ilmu Hukum, 2025)
The development of information and communication technology has driven digital transformation in various sectors of life, including in the world of employment and the right to wages is a fundamental right of workers guaranteed in the Indonesian labor law system. Wages are not only seen as a reward for work, but also as an instrument of social protection and a guarantee of the well being of the worker and his family. This study uses normative legal research methods. The problem in this paper is the legal regulation of workers 'wage rights in the Indonesian labor system based on applicable laws and regulations and the implications of digital transformation on the fulfillment and protection of workers wage rights viewed from the perspective of legislation. In conclusion, the legal regulation of workers wage rights in the Indonesian labor system has been comprehensively regulated through the Constitution of the Republic of Indonesia in 1945, the labor law, the job creation law, and government regulations on wages and digital transformation have significant implications for the fulfillment and protection of workers wage rights, especially due to the emergence of new work models that are not fully in accordance with the concept of Labor Relations in labor legislation. Suggestions, the government needs to strengthen supervision and enforcement of the law on the implementation of the wage system so that workers rights to wages can be optimally fulfilled and needs to update and strengthen labor regulations that specifically regulate digital workers and technology-based wage systems, including affirmation of employment relationship status.